Antibacterial Au nanostructured surfaces. Issue 5 (9th December 2015) - Wu, Songmei; Zuber, Flavia; Brugger, Juergen; Maniura-Weber, Katharina; Ren, Qun
Abstract : We present here a technological platform for engineering Au nanotopographies by templated electrodeposition on antibacterial surfaces. Abstract : We present here a technological platform for engineering Au nanotopographies by templated electrodeposition on antibacterial surfaces. Three different types of nanostructures were fabricated: nanopillars, nanorings and nanonuggets. The nanopillars are the basic structures and are 50 nm in diameter and 100 nm in height. Particular arrangement of the nanopillars in various geometries formed nanorings and nanonuggets. Flat surfaces, rough substrate surfaces, and various nanostructured surfaces were compared for their abilities to attach and kill bacterial cells. Methicillin-resistant Staphylococcus aureus, a Gram-positive bacterial strain responsible for many infections in health care system, was used as the model bacterial strain. It was found that all the Au nanostructures, regardless their shapes, exhibited similar excellent antibacterial properties. A comparison of live cells attached to nanotopographic surfaces showed that the number of live S. aureus cells was <1% of that from flat and rough reference surfaces. Our micro/nanofabrication process is a scalable approach based on cost-efficient self-organization and provides potential for further developing functional surfaces to study the behavior of microbes on nanoscale topographies.